A layered approach: integrating email security with document management processes. (December 2016) - Russell, Roy
Abstract : Security attacks today are rampant, exceedingly sophisticated and commonplace. Despite their best efforts, security professionals simply aren't able to impede the onslaught of the ever-increasing volume and maliciousness of cyber-attacks. And there are many manifestations of these attacks – bots, exploit kits, phishing, whaling, ransomware and so on. Organisations face many forms of attack, including exploit kits, phishing, whaling, ransomware and so on. But many of them revolve around email scams. Most organisations already deploy email security solutions to protect against malware and ensure business continuity in the event of a breach. But most neglect the next layer of security and fail to implement a document and email management system to house confidential and business-critical information. It is a major oversight, says Roy Russell of Ascertus.